Analisis Statistika Multivariat untuk Menilai Keterkaitan Gaya Hidup Digital dengan Tingkat Stres Mahasiswa - Rusliadi Rusliadi; Mohamad Sofie (Jurnal Pengabdian Dian Mandala, 2025)
Digital lifestyle has become an integral part of university students' daily lives, involving the use of social media, digital devices, and digital content consumption. The development of digital technology has positive impacts, facilitating easy access to information and social interactions. However, excessive use can lead to digital stress, which negatively affects students' mental health. This study aims to identify the key factors influencing students' digital lifestyles and analyze their relationship with stress levels. A quantitative approach with a survey method was employed, using a questionnaire to measure digital lifestyle, including social media usage frequency and digital device interaction duration, along with the Perceived Stress Scale (PSS) to measure students' stress levels. The factor analysis results show that social media usage and prolonged interaction with digital devices are significant factors contributing to students' stress. Furthermore, sleep disturbances and social anxiety were identified as other significant factors associated with increased stress. The multivariate regression analysis confirmed that students who spent more time on social media reported higher stress levels, associated with social anxiety and sleep disturbances caused by digital addiction. This study suggests the importance of managing digital device usage and raising students' awareness of the negative impacts of excessive social media use. The findings imply the need for support from universities and mental health organizations to provide interventions that help students manage their digital lifestyles, reduce stress, and improve their mental well-being.